Reactions to Cognitive Ability Tests: The Relationships between Race, Test Performance, Face Validity, and Test-Taking Motivation - CHAN, David (Institutional Knowledge at Singapore Management University, 1997)
The relationships among race, face validity perceptions, test-taking motivation, and test performance on a cognitive ability test were examined. Undergraduates completed 2 parallel cognitive ability tests and a test reactions measure. Results showed that test-taking motivation was related positively to subsequent performance on a parallel test even after the effects of race and performance on the first test were controlled. The effect of race on subsequent test performance was found to be mediated partially by motivation that provided evidence that some portion of the Black-White difference in test performance may be explained through differences in test-taking motivation. Results also indicated that Black-White differences in face validity perceptions of the test may be a function of Black-White differences in test performance. Face validity perceptions of the test affected subsequent performance on the parallel test but only indirectly through test-taking motivation.